2000
DOI: 10.1002/1097-0290(20001205)70:5<491::aid-bit3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of compressed and supercritical solvents on thermophilic microbial metabolism

Abstract: Selection of biocompatible solvents is critical when designing bioprocessing applications for the in situ biphasic extraction of metabolic end‐products. The prediction of the biocompatibility of supercritical and compressed solvents is more complicated than for liquid solvents, because their properties can change significantly with pressure and temperature. The activity of the anaerobic thermophilic bacterium, Clostridium thermocellum, was studied when the organism was incubated in the presence of compressed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The concern that CO 2 alters the pH of medium, leading to possible adverse affects on cells, promoted us to utilize low pressure N 2 for bioassembly. N 2 is inert, hinders oxidation, has little effect on cells, proteins, and on the metabolic activity within biological substances 34, 35. Low pressure N 2 did not change the pH value in medium, making it more suitable for bioassembly microstructures containing pH‐sensitive cells, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The concern that CO 2 alters the pH of medium, leading to possible adverse affects on cells, promoted us to utilize low pressure N 2 for bioassembly. N 2 is inert, hinders oxidation, has little effect on cells, proteins, and on the metabolic activity within biological substances 34, 35. Low pressure N 2 did not change the pH value in medium, making it more suitable for bioassembly microstructures containing pH‐sensitive cells, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we have demonstrated that high-pressure biphasic incubations lead to phase toxicity (due to the presence of the water/solvent interface), which may be the primary cause of cell inactivation with compressed solvents in both nongrowing 8,9 and growing 41 Clostridium thermocellum . The traditional predictor of biocompatibility in the presence of a solvent, the octanol/water partition coefficient (log P ), is nearly constant with pressure and solvent phase and is only a weak function of temperature for compressed ethane, propane, CO 2 , and N 2 at the conditions investigated . In our previous work, we observed cell inactivation in the presence of liquid propane and minimal inactivation in the presence of gaseous propane, despite the fact that propane has the same log P value in both the gaseous and the liquid state.…”
Section: Resultsmentioning
confidence: 77%
“…Compressed and supercritical fluids are increasingly used as alternative solvents for bioprocessing based on their pressure-tunable solvent strength and the ability to recover a solvent-free product following system depressurization. , Compressed or supercritical CO 2 ( T c = 304 K, P c = 7.4 MPa) offers the additional benefits of being nonflammable, nontoxic, inexpensive, and suitable for the processing of thermally labile compounds, such as pharmaceuticals. Successful applications of compressed solvents in bioprocesses include enzymatic and whole-cell biocatalysis, inverse emulsion protein extraction, and antisolvent precipitation of proteins , and the microbial sterilization of bulk aqueous phases and biodegradable polymeric matrixes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical fluid technology can be employed to eliminate the mass‐transfer resistance existing in biphasic systems (1, 2). The relevant research dates back to the late 1980s (2−11).…”
Section: Introductionmentioning
confidence: 99%